Age and Other Risk Factors Influencing Long-Term Mortality in Patients With Traumatic Cervical Spine Fracture. (1st May 2018) - Bank, Matthew; Gibbs, Katie; Sison, Cristina; Kutub, Nawshin; Papatheodorou, Angelos; Lee, Samuel; Stein, Adam; Bloom, Ona
Objective: To identify clinical or demographic variables that influence long-term mortality, as well as in-hospital mortality, with a particular focus on the effects of age. Summary and Background Data: Cervical spine fractures with or without spinal cord injury (SCI) disproportionately impact the elderly who constitute an increasing percentage of the US population. Methods: We analyzed data collected for 10 years at a state-designated level I trauma center to identify variables that influenced in-hospital and long-term mortality among elderly patients with traumatic cervical spine fracture with or without SCI. Acute in-hospital mortality was determined from hospital records and long-term mortality within the study period (2003-2013) was determined from the National Death Index. Univariate and multivariate regression analyses were used to identify factors influencing survival. Results: Data from patients (N = 632) with cervical spine fractures were analyzed, the majority (66%) of whom were geriatric (older than age 64). Most patients (62%) had a mild/moderate injury severity score (ISS; median, interquartile range: 6, 5). Patients with SCI had significantly longer lengths of stay (14.1 days), days on a ventilator (3.5 days), and higher ISS (14.9) than patients without SCI ( P < .0001 for all). Falls were the leading mechanism of injury for patients older than age 64. Univariate analysis identified that long-term survival decreased significantly for all patients older than age 65 (hazard ratio [HR]: 1.07; P < .0001). Multivariate analysis demonstrated age (HR: 1.08; P < .0001), gender (HR: 1.60; P < .0007), and SCI status (HR: 1.45, P < .02) significantly influenced survival during the study period. Conclusion: This study identified age, gender, and SCI status as significant variables for this study population influencing long-term survival among patients with cervical spine fractures. Our results support the growing notion that cervical spine injuries in geriatric patients with trauma may warrant additional research.